2013
DOI: 10.1111/febs.12587
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid delivery by cell penetrating peptides derived from dengue virus capsid protein: design and mechanism of action

Abstract: Cell penetrating peptides (CPPs) can be used as drug delivery systems for different therapeutic molecules. In this work two novel CPPs, pepR and pepM, designed from two domains of the dengue virus (DENV) capsid protein, were studied for their ability to deliver nucleic acids into cells as non-covalently bound cargo. Translocation studies were performed by confocal microscopy in HepG2, BHK and HEK cell lineages, astrocytes and peripheral blood mononuclear cells. Combined studies in HepG2 cells, astrocytes and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 77 publications
1
42
0
Order By: Relevance
“…The intracellular distribution of Cy3 labelled siRNA delivered using our D2C protein preparation, in C6/36 cells and BHK-21 cells, appeared to be comparable to the observations of Freire et al (2014) using the same protein derived from a different DENV2 strain (Freire et al, 2013), and those of Choi et al (2011) using the Hepatitis B virus capsid protein, as the siRNA nanocarrier. We have successfully demonstrated that DENV2 targeted siRNA, encapsulated in D2C, can inhibit DENV2 infection with comparable efficiency as that of a widely used commercial siRNA transfection reagent, HiPerfect, in the human liver cell line, Huh-7.…”
Section: D2c Protein As An Sirna Carrier For Anti Dengue Viral Applicsupporting
confidence: 69%
See 3 more Smart Citations
“…The intracellular distribution of Cy3 labelled siRNA delivered using our D2C protein preparation, in C6/36 cells and BHK-21 cells, appeared to be comparable to the observations of Freire et al (2014) using the same protein derived from a different DENV2 strain (Freire et al, 2013), and those of Choi et al (2011) using the Hepatitis B virus capsid protein, as the siRNA nanocarrier. We have successfully demonstrated that DENV2 targeted siRNA, encapsulated in D2C, can inhibit DENV2 infection with comparable efficiency as that of a widely used commercial siRNA transfection reagent, HiPerfect, in the human liver cell line, Huh-7.…”
Section: D2c Protein As An Sirna Carrier For Anti Dengue Viral Applicsupporting
confidence: 69%
“…pH shift assembly of adenoviral serotype 5 capsid protein nanosystems has been used for macromolecular delivery . Recently, E. coli expressed D2C protein and a D2C based peptide, designated Pep M, were shown to encapsulate and deliver siRNA into cultured cell lines, but target knockdown data was restricted to TLR-3 in endothelial cells (Freire et al, 2013(Freire et al, , 2014. The utility of D2C protein or its peptide derivatives for siRNA delivery in the context of any particular disease indication is not known at present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, recent data support an additional participation of DENV C protein in the virus genome internalization, a role that would be shared by all flaviviruses' capsid proteins. It has been found that recombinant DENV C protein as well as two synthetic peptides comprising C protein residues 45-72 and 67-100 were able to translocate short oligonucleotide sequences (ssDNA and siRNA) across cellular membranes (Freire et al, 2013b, Freire et al, 2014. More interestingly, large nucleic acids, such as a GFP-encoding plasmid, were not only transported into the cells but also expressed at levels comparable to those obtained when traditional transfection agents, such as lipofectamine, were used (Freire et al, 2013b).…”
Section: Hypothetical C Protein-mediated Rna Translocation Across Memmentioning
confidence: 99%